Nitrogen-Doped Carbon Coated WS2 Nanosheets as Anode for High-Performance Sodium-Ion Batteries - Liu, Yong; Wei, Huijie; Wang, Chao; Wang, Fei; Wang, Haichao; Zhang, Wanhong; Wang, Xianfu; Yan, Chenglin; Kim, Bok H.; Ren, Fengzhang (Frontiers in Chemistry, 2018)
Due to the cost-effectiveness of sodium source, sodium-ion batteries (SIB) have attracted considerable attention in recent years. However, SIB still have some challenges in in competing with lithium-ion batteries for practical applications. In particular, the high rate performance and long-term cycling are very difficult to be achieved for SIB. Here, nitrogen-doped carbon-coated WS2 nanosheets (WS2/NC) were successfully synthesized by high-temperature solution method, followed by carbonization of polypyrrole. When tested as anode materials for SIBs, WS2/NC composite displayed high rate capacity at 386 and 238.1 mAh g-1 at 50 and 2000 mA g-1, respectively. More importantly, even after 400 cycle, the composite electrode still can delivere a capacity of about 180 mAh g-1 at 1000 mA g-1, corresponding a capacity loss of 0.09% per cycle. The excellent electrochemical performance is attributed to the synergistic effect of highly conductive nature of the nitrogen-doped carbon-coating and WS2 nanosheets. Results demonstrated that the WS2/NC nanosheets are promising electrode materials for Sodium ion batteries application.